Emerging Consequences of Phubbing among Adults - Ramesh Nagarajappa1, Debasruti Naik2, Gayathri Ramesh3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
In recent years phubbing activities have affected both phubers and phubees’. It has ruined the real-life socialrelationships. People who are busy in phubbing believes that smartphones are now a daily part of theirinterpersonal communication. In simple words, instead of giving much consideration to the people, there isa social place, they opt to bolt their eyes on their mobile phones while interacting with people. Phubbing is athreat to the mental health which leads to depression, anxiety and causes a negative impact on relationships.This review article focuses on the effects and signs of phubbing and how to overcome it.